Prototype Aplikasi Informasi Oleh-Oleh Di Purwokerto Dengan Menerapkan Metode User Experience Lifecycle - Melani Eka Rahayu; Gita Fadila Fitriana; Ariq Cahya Wardhana (UNIVERSITAS INDO GLOBAL MANDIRI)
The Information Application for Souvenirs in Purwokerto is a mobile-based application that can be used to find information about souvenirs and gift shops in the city of Purwokerto. This application is intended for local tourists, immigrants and local residents to make it easier to find souvenirs in Purwokerto. Of course, when discussing travel or tourism, it cannot be separated from souvenirs, souvenirs, or souvenirs. This application is designed to provide information about souvenirs in the city of Purwokerto from products, shops, location of gift shops, prices for souvenirs and others. This study designed a prototype of information application for souvenirs in Purwokerto using the User Experience Lifecycle method, the method proposed by Hartson and Pyla to develop user experience with an emphasis on usability and user experience aspects. This method is divided into four stages, namely analysis, design, prototype, and evaluation. Testing in this study uses usability testing on the results of the medium fidelity level prototype with the System Usability Scale (SUS) method at the evaluation stage. The results of usability testing using the SUS method get a score of 74.17 or B (Good) where the score meets the minimum standard of the SUS score of 68. Usability measurement on the prototype application for souvenirs in Purwokerto has met the efficiency level with an overall relative efficiency value of 88 .5%, and the percentage effectiveness level is 91.3% of the results of task completion by all respondents. Thus the application prototype for souvenirs in Purwokerto has met the usability value in terms of efficiency, effectiveness and satisfaction. Based on this, this research has succeeded in applying the User Experience Lifecycle method to application design and usability testing with the System Usability Scale (SUS) which has exceeded the minimum standard. Therefore, the application design for souvenirs in Purwokerto based on user experience and needs can be carried out to the application development or production stage. Keywords : Gift, Application Prototype, User Experience Lifecycle, Usability, System Usability Scale (SUS)